Analisis Kelayakan Bisnis pada Perancangan dan Pengembangan Produk Kursi Multifungsi - Lestari, Lugina; Wahyudin, Wahyudin (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2022)
The processing of chair products has dominated demand in Indonesia, requiring manufacturers to always be able to develop product innovations. Multifunctional chairs that can be a product renewal can be an opportunity for the market. To find out what consumers want and the feasibility of this business, a study was conducted on the design and development of multifunctional chair products based on consumer needs and the feasibility of a business that will be run in 2021-2023 in Subang district. This study aims to design and develop products in a structured manner according to the needs and expectations of consumers and to analyze the business feasibility of multifunctional chair products. The method used is quantitative, namely by using Quality Function Deployment (QFD) and business feasibility aspects with a multifunctional chair product analysis unit. The results of the approach using QFD show that there are 6 product characteristics along with 3 product dimensions for designing a multifunctional chair product with the highest absolute and relative weight owned by the dimensions of the beauty of the product. While the results obtained based on the feasibility study obtained NPV > 0, Rp. 323,684,304.9, IRR value > deposit interest of 99.4%, Net B/C value > 1 of 1.19, payback period of less than 2 years, namely 23 months and BEP of 7 units. Based on this, it is stated that the business of making multifunctional chair products is feasible, so that the business can be run.